Anti-Inflammatory Effects of Eicosapentaenoic Acid and Docosahexaenoic Acid Derived from Patin Fish Oil on Diabetic Nephropathy: A Bioinformatics Study - Purnomo, Doddy Aditya; Awidarta, Kevin; Nugroho, Agung Endro; Rohman, Abdul (Journal of Food and Pharmaceutical Sciences, 2026)
Diabetic nephropathy is a severe complication of diabetes mellitus with a significant global impact on end-stage renal disease. Fish-derived fatty acids show promise in inflammatory disorders, but their mechanisms in diabetic nephropathy remain unclear. This study used network pharmacology and molecular docking to investigate the therapeutic targets of EPA and DHA from Patin fish oils. Potential targets of EPA and DHA were retrieved from the Swiss Target Prediction, SEA, and SuperPRED databases, identifying 160 and 185 targets, respectively. Notably, 37 and 62 of these targets overlapped with DN-related targets from GeneCards, DisGeNET, and OMIM. Protein-protein interaction (PPI) network analysis revealed hub genes, including PPARG, TLR4, and TP53, as critical mediators. Gene Ontology (GO) enrichment analysis revealed involvement in biological processes such as collagen metabolic process for EPA and regulation of inflammatory response for DHA, while KEGG pathway analysis highlighted the modulation of PPAR signaling, the renin-angiotensin system, and the AGE-RAGE signaling pathway. Molecular docking confirmed favorable binding affinities of EPA and DHA to key targets such as PPARG (-8.04 kcal/mol for DHA) and PPARD (-8.11 kcal/mol for EPA). These findings suggest that EPA and DHA may mitigate DN-associated inflammation through multi-target and multi-pathway interactions, positioning them as potential supplementary therapeutic agents.